2001
DOI: 10.1002/ps.351
|View full text |Cite
|
Sign up to set email alerts
|

Finite dose diffusion studies: III. Effects of temperature, humidity and deposit manipulation on NAA penetration through isolated tomato fruit cuticles

Abstract: Effects of temperature, humidity, rewetting and removal of deposits on penetration of NAA [2-(1-naphthyl)acetic acid] through isolated tomato (Lycopersicon esculentum Mill) fruit cuticles were studied using a finite dose diffusion system. In this system, an aqueous 5-microliter droplet (0.1 mM NAA in 20 mM citric acid buffer) is applied to the outer surface of a cuticle, which is mounted in a glass diffusion half-cell. The cell wall surface is in contact with a receiver solution (20 mM citrate). Penetration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Additionally, several approximations were required because of the lack of K d values for the cuticle components. K d,PC1 (48,880 L/Kg) was determined and employed to represent K d,EW because its sorption capability was equivalent to those of intact components after dewaxing 34 41 48 49 52 . This value was calculated through the regression of the sorption isotherm of intact green pepper fruit cuticle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, several approximations were required because of the lack of K d values for the cuticle components. K d,PC1 (48,880 L/Kg) was determined and employed to represent K d,EW because its sorption capability was equivalent to those of intact components after dewaxing 34 41 48 49 52 . This value was calculated through the regression of the sorption isotherm of intact green pepper fruit cuticle.…”
Section: Resultsmentioning
confidence: 99%
“…The superior organic pollutant-sorption capacities of EW and CP slowed the diffusion of organic pollutants but created sharp concentration gradients within the plant cuticular membrane, which likely supplied a stable driving force and eventually caused linear penetration. This endogenous driving force increased as the penetration rate of pollutants into CP, which mainly consisted cutin, a superior reservoir for organic pollutants, increased 49 52 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the spatial separation between the AIs and the adjuvants might directly or indirectly influence the penetration of the compounds and their biological efficacy. For instance, several studies have shown the importance of the relative humidity for the penetration of the active ingredients 45–48. However, little or no attention has been paid to the deposit structure,49 and thus the hypothesis cannot be excluded that much of the unexplained variation in herbicide uptake arises from the differences in the physical form of the dry deposits 4.…”
Section: Discussionmentioning
confidence: 99%
“…In polymer science, hydrophobicity and surface hydration govern many applications . In agrochemistry, the efficacy of foliage-applied agrochemicals depends on the amount of active ingredients delivered into the target species and/or tissues across the cuticle layer, which forms a natural interface between the plant and the environment. , Plant cuticle is a thin (<0.1–10 μm) continuous layer or membrane of predominantly lipid material that covers the entire external surface of plants. This barrier is constituted of three cuticular hydrophobic components arranged as layers: the epicuticular wax, the cuticle proper, and the cuticular layer .…”
Section: Introductionmentioning
confidence: 99%